2022
DOI: 10.1177/00033197221105745
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Liver Fibrosis Scores Are Associated With Contrast-Associated Acute Kidney Injury in Patients Undergoing Elective Percutaneous Coronary Intervention

Abstract: Previous studies have demonstrated that non-invasive liver fibrosis scores (LFSs) are associated with kidney function deterioration. This study aimed to assess the predictive performance of LFSs in contrast-associated acute kidney injury (CA-AKI) in coronary artery disease (CAD) patients undergoing elective percutaneous coronary intervention (PCI). This retrospective study involved 5627 patients. The frequency of CA-AKI was 6.3% (n = 353). In a multivariate logistic analysis after adjustment, non-invasive LFSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…De Ritis ratio is a readily available marker of liver disease 2 . An association of De Ritis ratio with an increased risk of mortality has been reported in patients with acute myocardial infarction, 15,16 type 2 diabetes, 27 arterial hypertension, 28 and contrast‐induced acute kidney injury after elective PCI 29 . So far, only one study (a retrospective cohort of 203 patients with stable CAD analysed over a mean follow‐up of 749 days) has assessed the association between De Ritis ratio and mortality in patients with stable CAD after elective PCI 17 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…De Ritis ratio is a readily available marker of liver disease 2 . An association of De Ritis ratio with an increased risk of mortality has been reported in patients with acute myocardial infarction, 15,16 type 2 diabetes, 27 arterial hypertension, 28 and contrast‐induced acute kidney injury after elective PCI 29 . So far, only one study (a retrospective cohort of 203 patients with stable CAD analysed over a mean follow‐up of 749 days) has assessed the association between De Ritis ratio and mortality in patients with stable CAD after elective PCI 17 .…”
Section: Discussionmentioning
confidence: 97%
“…2 An association of De Ritis ratio with an increased risk of mortality has been reported in patients with acute myocardial infarction, 15,16 type 2 diabetes, 27 arterial hypertension, 28 and contrast-induced acute kidney injury after elective PCI. 29 So far, only one study (a retrospective cohort of 203 patients with stable CAD analysed over a mean follow-up of 749 days) has assessed the association between De Ritis ratio and mortality in patients with stable CAD after elective PCI. 17 In this study, a De Ritis ratio of ≥1.4 was associated with approximately threefold higher adjusted hazard for all-cause mortality compared with patients in the lower De Ritis ratio.…”
Section: F I G U R E 1 Kaplan-meier Curves Of Mortality Hr Hazard Ratiomentioning
confidence: 99%
“…In this retrospective study, which included 5627 patients, CIN developed in 353 (6.3%) patients. The preoperatively calculated FIB-4 scores and APRI values were shown to be significantly associated with the development of CIN [ 15 ]. We also found a significant relationship in our study between high FIB-4 scores and APRI values and the development of CIN in patients who had undergone elective EVAR procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Since clinical features and event rates were similar to other reports, 8,9,[15][16][17]23,24 we believe that our results might be representative and useful in clinical practice beyond the single-center studies previously reported. 16,[25][26][27][28][29][30] Early risk stratification and structured discharge planning of STEMI patients have gained interest in the last years 12,13 and, moreover, through the COVID-19 pandemic. 6 Adoption of this treatment strategy could reduce hospital costs, resource utilization, and enhance patient satisfaction without affecting outcome.…”
Section: Discussionmentioning
confidence: 99%